Development of Holy Basil Storage Using Low Temperatures and Modified Atmosphere Packaging - Tosapol Niamthong; Sukasem Sittipod; Vanee Chonhenchob (Agriculture and Natural Resources, 2007)
Holy basil (Ocimum sanctum L.) is an herbal produce which rapidly deteriorates after harvesting, thus giving a short shelf life. Different levels of low temperature storage in combination with modified atmosphere packaging were used in this study to extend its shelf life. Holy basil branches of 80 g were packed in 4 different types of bag: a commercial polypropylene film with perforated holes and 3 other various oxygen permeability films, which are very high (PE-3), high (PE-2) and medium (PE-1). All packed sample were stored at 5, 10 and 25°C, then randomly sampled on day 3, 7, 11 for quality checking. The results showed the holy basil stored at 5°C faced with a rapid and severe chilling injury symptom; exhibited by browning spots and water soaking area. At the 25°C storage, basil yellowing and weight loss were very rapid due to high dehydration rate. The optimal temperature for storing holy basil was 10°C. Polypropylene films with holes contribute to faster weight loss and shorter shelf life than the other three packages. Oxygen remained in head space of PE-3, PE-2 and PE-1 bags were found at 18%, 17%, and 11%, respectively while carbon dioxide also were found at 0.7%, 0.8% and 1.8%, respectively. Modified atmosphere packaging at 10°C was found to be able to keep holy basil at a satisfactory quality for 9 days.